Resistensi Larva Strongyle sp. Terhadap Albendazole pada Kambing Kacang (Capra hircus) di Indonesia - Natasha Imanuelle; Meity M Laut; Dede Rival Novian (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2023)
Nematodiasis is a disease of livestock which caused by nematode infestation. Nematodes in the digestive tract inhibit livestock productivity and increase mortality in young animal. Generally speaking, control of nematodiasis is done by administering anthelmintic from benzimidazole group. Albendazole is the most commonly used anthelmintic. However, continuous use of albendazole in ruminants leads to the development of resistance. The present study aims to not only investigate and evaluate Strongyle sp. larvae resistance to albendazole in Indonesia but also to determine the incident rate of albendazole resistance. This study and references were obtained through Google Scholar and PubMed then arranged using Mendeley. The references are scientific journals, scientific articles, Ebooks and proceedings with